Exploring change processes in compassion focused therapy in psychosis: Results of a feasibility randomized controlled trial. (24th October 2012) - Braehler, Christine; Gumley, Andrew; Harper, Janice; Wallace, Sonia; Norrie, John; Gilbert, Paul
<x xml:space="preserve">Abstract</x> Objectives Compassion focused therapy (CFT) was developed to stimulate capacities for soothing and affiliation to self and others as a way to regulate the threat system. This feasibility study aimed to assess the safety, the acceptability, the potential benefits, and associated change processes of using group CFT with people recovering from psychosis. Design A prospective, randomized, open‐label, blinded end point evaluation design was used. Method Forty adult patients with a schizophrenia‐spectrum disorder were randomized to CFT plus treatment as usual (TAU; n = 22) or to TAU alone (n = 18). Group CFT comprised 16 sessions (2 hr each, 1 x week). Participants were assessed prior to randomization and at the end of treatment. Assessments included semi‐structured interviews to elicit narratives of recovery from psychosis and self‐report measures. At the end of treatment, participants were rated on the Clinical Global Impression Scale. Narratives were coded using the Narrative Recovery Style Scale to provide measures of change in compassion and avoidance. Change processes were correlated with changes in depression, personal beliefs about illness, fear of recurrence, and positive and negative affect. Results Group CFT was associated with no adverse events, low attrition (18%), and high acceptability. Relative to TAU, CFT was associated with greater observed clinical improvement (p < 0.001) and significant increases in compassion (p = 0.015) of large magnitude. Relative to TAU, increases in compassion in the CFT group were significantly associated with reductions in depression (p = 0.001) and in perceived social marginalization (p = 0.002). Discussion Findings support the feasibility of group CFT in psychosis and suggest that changes in compassion can be achieved, which appear to reduce depression in particular. This is the first randomized controlled evaluation of CFT. Conclusion Compassion focused therapy appears as a safe, acceptable, promising, and evolving intervention for promoting emotional recovery from psychosis. Practitioner Points Compassion focused therapy appears safe to use with people recovering from psychosis. Compassion focused therapy was associated with significantly greater clinical improvement than Treatment as Usual. Relative to TAU, CFT was associated with a significant increase in compassion of large magnitude. Relative to TAU, in the CFT group increases in compassion were significantly associated with reductions in depression and in perceived social marginalization.